2023
DOI: 10.1186/s12904-023-01187-4
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of knowledge, attitude and behavior in children’s palliative care among pediatric healthcare workers: a cross-sectional survey in China

Abstract: Background Palliative care has become a key medical field worldwide. Although research relating to adult palliative care is well-established, less is known about children’s palliative care (CPC). Therefore, this study investigated the knowledge, attitude and behavior of pediatric healthcare workers (PHWs) regarding CPC and analyzed the influencing factors for the implementation and development of CPC. Methods A cross-sectional survey of 407 PHWs wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Specifically, in our study, Chinese pediatricians reported that they lacked supportive policies/guidelines for PPC implementation. This was consistent with Zhu et al who also reported a lack of supportive PPC policies/guidelines for healthcare providers [ 30 ]. A survey study [ 28 ] and a secondary data analysis study [ 25 ] identified lack of supportive policies/guidelines as the largest barrier to PPC implementation in Mainland China.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, in our study, Chinese pediatricians reported that they lacked supportive policies/guidelines for PPC implementation. This was consistent with Zhu et al who also reported a lack of supportive PPC policies/guidelines for healthcare providers [ 30 ]. A survey study [ 28 ] and a secondary data analysis study [ 25 ] identified lack of supportive policies/guidelines as the largest barrier to PPC implementation in Mainland China.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, improving unit support where pediatricians work could facilitate PPC implementations. A previous Chinese survey study found that healthcare providers working in modern, well-equipped facilities having advanced medical resources were more likely to have opportunities to practice PPC [ 30 ]. Additionally, two other qualitative studies stressed the importance of unit support on PPC implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of palliative care services for patients remains low, and a systematic understanding of the assessment content and tools required for palliative care needs is lacking [ 5 , 6 ]. Compared with other countries, the practice of PPC in China is in its early stages; thus, service resources are insufficient, and the service model is relatively simple [ 7 ]. Preliminary exploration efforts began in Beijing, Shanghai, Chengdu, Changsha, and other cities, in addition to Hong Kong, Macao, and Taiwan [ 8 ].…”
Section: Introductionmentioning
confidence: 99%